2022
DOI: 10.48550/arxiv.2201.03380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bounded Space Differentially Private Quantiles

Abstract: Estimating the quantiles of a large dataset is a fundamental problem in both the streaming algorithms literature and the differential privacy literature. However, all existing private mechanisms for distribution-independent quantile computation require space at least linear in the input size 𝑛. In this work, we devise a differentially private algorithm for the quantile estimation problem, with strongly sublinear space complexity, in the one-shot and continual observation settings. Our basic mechanism estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One limitation of this work is the requirement of considering a parametric distribution family for the population distribution. Estimation of characteristics regarding non-parametric distributions, such the as mean and quantiles, is also a fundamental problem for data streaming applications (Dwork and Lei, 2009;Alabi et al, 2022). A useful extension of this work would be an online estimation methodology of (characteristics) non-parametric distributions.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this work is the requirement of considering a parametric distribution family for the population distribution. Estimation of characteristics regarding non-parametric distributions, such the as mean and quantiles, is also a fundamental problem for data streaming applications (Dwork and Lei, 2009;Alabi et al, 2022). A useful extension of this work would be an online estimation methodology of (characteristics) non-parametric distributions.…”
Section: Discussionmentioning
confidence: 99%
“…A sketch for fractional frequency moments F p for 0 ≤ p ≤ 1 has been given by Wang, Pinelis, and Song [27]. A sketch for differentially private quantiles has been given by Alabi, Ben-Eliezer, and Chaturvedi [1]. A technique for stream sanitization has been given by Kaplan and Stemmer [17]; this work resulted in improved differentially private sketches for approximate quantiles.…”
Section: Related Workmentioning
confidence: 99%
“…One of the main difficulties is that most sublinear-time and streaming algorithms are randomized and give only probabilistic guarantees on the quality of the output. This makes adding noise based on global sensitivity 1 -which is commonly used to get differentially private algorithms -unsuitable for this situation, as in the worst case the global sensitivity of the approximation algorithm 2 is very large even if the global sensitivity of the function being approximated is small. In this paper, we propose a way to get around this issue by showing additive noise mechanisms that only need that (1) the function being approximated has low global sensitivity and (2) the answer of the algorithm is sufficiently concentrated around the true value.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have observed that some data sketches are inherently differentially private [Blocki et al, 2012, Smith et al, 2020, while many other data sketches need modifications to the algorithm to be differentially private. In particular, a substantial amount of literature has focused on differentially private data sketches for tasks such as linear algebra [Upadhyay, 2014, Arora et al, 2018, cardinality estimation [Mir et al, 2011, Pagh and Stausholm, 2020, Dickens et al, 2022 and quantile approximation [Tzamos et al, 2020, Gillenwater et al, 2021, Alabi et al, 2022.…”
Section: Introductionmentioning
confidence: 99%